The Implementation of PBL (Problem Based Learning) and POE (Predict, Observe, Explain) Models: Their Impact on Critical Thinking Abilities - Ihsan Khoirul Anam; Epon Ningrum; Iwan Setiawan; Herdien Raka Moch Isya (Jurnal Pendidikan Ilmu Sosial, 2024)
Learning models that can develop critical thinking skills include the PBL and POE learning models. The purpose of this study was to analyze the effect of using the PBL and POE learning models on critical thinking skills in SMA Negeri 1 Bandung. This study used an experimental research method with a quasi-experimental design (none equivalent groups pretest-posttest design). Data collection was carried out by tests, assignments, and observation sheets. The subjects in this study were students of XI IPS class at SMA Negeri 1 Bandung. The results showed that 1) there were differences in the critical thinking abilities of students in experimental class 1 before and after using the PBL learning model, 2) there were differences in the critical thinking abilities of students in experimental class 2 before and after using the POE learning model, 3) there were differences students' critical thinking skills between experimental class 1 using the PBL learning model and experimental class 2 using the POE learning model, 4) there is an effect of using the PBL learning model on students' critical thinking skills in experiment 1, 5) there is an effect of using the POE learning model on students' critical thinking skills in experimental class 2.